Energy Resources, Greenport, and Modern Technology in the Port Terminal Operational Business Efficiency - Nur Widyawati; Muhammad Dany Ardyansyah (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This study aims to determine the effect of energy resources, greenport, and modern technology on the efficiency of port terminal operational business. Design / methodology / approach: This study uses a quantitative approach with multiple linear regression analysis techniques. Findings: The research was carried out at the Gresik port terminal. Research limitations / implications: Limitations in this study using three independent variables and one variable. The independent variables are energy resources, greenport and technology. The variable in question is business efficiency. Practical Implications: The population in this study were all operators and employees in the operational division with a total sample of 57 respondents. Originality / Value: This research was conducted at the Port of Gresik Paper type: Research paper